Pengaruh Semangat Kerja Terhadap Kinerja Karyawan Bagian Gudang Pada PT Capella Dinamik Nusantara Pekanbaru - Imrialis, Imrialis (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research aims to determine the influence of work enthusiasm on the performance of warehouse employees at PT. Capella Dinamik Nusantara. The sample in this research was 34 people with quantitative data processing methods. The results of this research hypothesis test are t count 3.945 > 2.03452 and also a significance level of 0.000 < 0.005. And the results of the hypothesis test in this research are that work morale has a significant effect on the performance of warehouse employees at PT Capella Dinamik Nusantara. The simple regression equation is as follows Y = 29.604 + 0.547 Meanwhile, the relationship between work morale and employee performance in the warehouse section of PT Capella Dinamik Nusantara is positive as evidenced by the results of the regression coefficient (b) of 0.547, which means that every increase in work morale in the warehouse section of PT Capella Dinamik Nusantara Besar influences work morale on employee performance in the warehouse section. PT Capella Dinamik Nusantara is 32.7%.